2016
DOI: 10.3168/jds.2015-10052
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Effect of diet changes on sorting behavior of weaned dairy calves

Abstract: Dairy cows sort mixed rations; in some cases sorting can lead to digestive disorders. How sorting behavior develops in calves is poorly understood. The objective of this observational study was to determine if sorting behavior of total mixed ration (TMR)-fed dairy calves was affected by the removal of supplementary concentrate. Dairy bull calves (n=18) were provided access to both a TMR (49.1% dry matter) and calf starter fed separately during the preweaning period starting at 3 d of age. Sorting of the TMR wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…These results indicate that calves begin to sort the feed immediately following transition to a mixed diet, and they prefer the feed component they were initially familiar with. In agreement with current study, previous studies also revealed that feed sorting behavior was observed in both milk-feeding [45] and weaned calves [46], suggesting that feeding and sorting behaviors are established early in life even though the brain and digestive system are not fully developed at this stage. It was not surprising to find that calves were in favor of feed components which they had been exposed to earlier.…”
Section: Feed Sortingsupporting
confidence: 93%
“…These results indicate that calves begin to sort the feed immediately following transition to a mixed diet, and they prefer the feed component they were initially familiar with. In agreement with current study, previous studies also revealed that feed sorting behavior was observed in both milk-feeding [45] and weaned calves [46], suggesting that feeding and sorting behaviors are established early in life even though the brain and digestive system are not fully developed at this stage. It was not surprising to find that calves were in favor of feed components which they had been exposed to earlier.…”
Section: Feed Sortingsupporting
confidence: 93%
“…Calves are capable of developing the emergence and persistence, but not the pattern, of sorting skills from a young age, and these skills are determined by nutritional demands, rumen function, or their motivation to chew and ruminate (Costa et al, 2016). Because calves are thought to learn through physiological postingestive feedback mechanisms (Provenza, 1995), our findings indicate that calves fed AH and RAH from birth learn to balance nutrient intake (CP and NDF measured in the present study) in ways that support growth and alleviate the effects of lower rumen pH, which was substantiated by similar final BW (87.4 vs. 92.8 kg for AH vs. RAH, respectively; SEM = 3.25 and P = 0.26) and rumen fluid pH during the preweaning (5.62 vs. 5.73 for AH vs. RAH, respectively; SEM = 0.14 and P = 0.57) and postweaning (5.70 vs. 5.60 for AH vs. RAH, respectively; SEM = 0.09 and P = 0.45) periods between treatment groups (Kargar and Kanani, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, longer particles may increase both chewing and rumen pH, which may explain why dairy cows experiencing ruminal acidosis altered their preferences for the form of their alfalfa diet in favor of long-stemmed hay over pellets [ 10 ]. Likewise, both beef and dairy cattle preferentially sorted for longer feed particles [ 7 9 ] when suffering from acute bouts of ruminal acidosis, as did dairy calves when they were offered a total mixed ration in addition to their primary diet of high-energy calf starter [ 34 ]. In future studies of ruminant motivation to obtain roughage, it would be informative to quantify feed particle size.…”
Section: Discussionmentioning
confidence: 99%